Neutropenic complications in the PANTHER phase III study of adjuvant tailored dose-dense chemotherapy in early breast cancer. (2nd January 2020) - Papakonstantinou, Antroula; Hedayati, Elham; Hellström, Mats; Johansson, Hemming; Gnant, Michael; Steger, Günther; Greil, Richard; Untch, Michael; Moebus, Volker; Loibl, Sibylle; Foukakis, Theodoros; Bergh, Jonas; et al.
Abstract: Introduction: Myelosuppresion is a common side effect of chemotherapy and granulocyte-colony stimulating factor (G-CSF) is often used to reduce the risk of neutropenic events. The purpose of this exploratory analysis was to investigate neutropenic complications in the phase III PANTHER trial of standard 3-weekly chemotherapy with 5-fluorouracil, epirubicin and cyclophosphamide plus docetaxel (FEC/D) versus bi-weekly tailored dose-dense EC/D adjuvant chemotherapy in breast cancer. Patients and methods: Febrile neutropenia, neutropenic infection and infection grade 3–4 according to CTC AE 3.0, were explored in relation to G-CSF use. Per cycle analysis was performed concerning dose reduction and dose delays in conjunction with G-CSF administration. Results: In the experimental group, 98.9% of patients received primary G-CSF support during EC and 97.4% during docetaxel, compared with 49.7% during FEC and 63.88% during docetaxel in the standard group. Overall, the use of G-CSF was associated with a lower risk for developing neutropenic events (OR 0.44, 95% CI 0.35–0.55, p  < .001). Chemotherapy delays due to neutropenia and leukopenia were significantly decreased among patients that received G-CSF (OR 0.098, 95% CI 0.06–0.15 and OR 0.32, 95% CI 0.18–0.58, respectively). Discussion: In conclusion, G-CSF support reduces neutropenic events and permits increased relative dose intensity, which is essential for improved survival outcomes.